THE EFFECT OF BUREAUCRATIC DIGITALIZATION ON ADMINISTRATIVE BURDENS AND ACCESS TO PUBLIC SERVICES AMONG MARGINALIZED COMMUNITIES IN MAKASSAR CITY - Sumardi Sumardi; Kahar Gani; Anirwan Anirwan; Nasir Nasir; Abdul Halim (Natapraja, 2026)
This study examines the effects of bureaucratic digitalization on administrative burdens and access to public services among marginalized communities in Makassar City, Indonesia. While digital technologies are promoted to improve service efficiency, transparency, and accessibility, digitalization may also introduce new administrative challenges, especially for vulnerable groups. This research adopts a quantitative correlational design with structured questionnaires administered to 200 citizens and 50 public servants who have direct experience with digitalized public services. Data were analyzed using multiple linear regression, confirming that digitalization has a positive and significant impact on access to public services (B = 0.416, p < 0.001), indicating that digital systems enhance service availability. However, the analysis also reveals that digitalization increases administrative burdens (B = 0.174, p = 0.007), suggesting that marginalized communities face greater learning, compliance, and psychological costs. Multivariate analysis further supports that digitalization simultaneously affects both administrative burdens and service access. These findings highlight the dual nature of digital governance, where improvements in access may coincide with heightened administrative challenges. The study emphasizes the importance of inclusive digital design, adequate user support, and hybrid service models to ensure that bureaucratic digitalization benefits all citizens, particularly marginalized groups.